Potential benefits of metformin and pioglitazone combination therapy via gut microbiota and metabolites in high-fat diet-fed mice - Wang, Dongmei; Liu, Jieying; Zhong, Ling; Ding, Lu; Zhang, Qian; Yu, Miao; Li, Ming; Xiao, Xinhua (Frontiers in Pharmacology, 2022)
Metformin and pioglitazone monotherapy have been proven to alter gut microbiota in diabetes and obesity. The present study aimed to investigated whether the combined administration of pioglitazone and metformin achieved superior protective effects on high-fat diet (HFD)-fed obese mice and elucidated its molecular mechanism via the gut microbiota and its metabolites. C57BL/6 males were randomly divided into five groups: the control group, fed a normal control diet; the HFD group, fed an HFD; the metformin monotherapy group, fed an HFD and treated with metformin; the pioglitazone monotherapy group, fed an HFD and treated with pioglitazone; and the combination therapy group, fed an HFD and treated with metformin and pioglitazone combination therapy. The cecal contents were collected for 16S rDNA amplicon sequencing and untargeted metabolomics analysis. The results showed that the combination therapy of metformin and pioglitazone significantly improved insulin sensitivity and glucolipid metabolism in HFD-fed mice. Combination therapy markedly altered gut microbiota by increasing beneficial bacteria, such as Bifidobacterium, Christensenellaceae_R-7_group, Faecalibacterium and Roseburia, and decreasing harmful bacteria, such as Oscillibacter and Eubacterium_xylanophilum_group. Fecal metabolites were significantly changed in the combination therapy group, including a reduction in amino acid metabolism and augmentation of lipid metabolism, such as citrulline, sarcosine, D-glutamine, lipoxin A4, prostaglandin E2, stearidonic acid and lucidenic acid A. These results revealed that combined metformin and pioglitazone therapy had synergistic effects or at least have an additive effect on modifying gut microbiota and metabolites, closely associated with improved glucolipid metabolic parameters in HFD-fed mice, which provides novel evidence and promising targets for metformin and pioglitazone combination therapy in type 2 diabetes.